Analisis Pengaruh Lean Construction Yang Dominan Terhadap Waste Yang Terjadi Pada Proyek Konstruksi Di Kota Palangka Raya - Yan, David; Nuswantoro, Waluyo (Jurnal Basement : Jurnal Teknik Sipil, 2024)
Construction projects are activities that take place within a limited time with certain resources to get the planned construction results, so in an effort to achieve good construction work results, various methods are needed in carrying out the work. Project management is a science related to leading and coordinating resources consisting of humans and materials using modern management techniques to achieve predetermined goals, namely within the scope of quality, schedule, and cost. The application of project management in the field still has many problems that occur and result in waste. To be able to minimize the occurrence of waste, the Ministry of Public Works and Public Housing through the Directorate General of Bina Konstruksi introduced lean construction techniques. The purpose of this study was to determine the most dominant influence of lean construction on waste that occurs in construction projects in Palangka Raya City. The research method used a questionnaire distributed to building contractors in Palangka Raya City. The research data used primary data obtained from respondents, data analysis using the dominant test of Standardized Coefficients Beta. The results of the analysis obtained that the most dominant lean construction variable is the Last Planning System variable of 28.7%.